EFEKTIFITAS METODE KOOPERATIF THINK PAIR SHARE TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN AGAMA ISLAM DI SDN WONOKROMO I SURABAYA - Maimunah, Siti (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
The research objective in this study was to determine the effect of the Think Pair Share learning model on learning motivation and learning outcomes of Class V SD Negeri Wonokromo Surabaya?. This study uses a quantitative method, with the type of experimental research, namely the Pre-Experiment Design with the One-Group Pretest-Posttest Design research design. data collection methods used interviews, tests, questionnaires and documentation. Questionnaire instruments to measure learning motivation and test instruments in the form of pre test and post test to measure learning outcomes. The questions were analyzed using the MANOVA test. The results of this study indicate that the think pair share cooperative learning model on the motivation and learning outcomes of Islamic religion is very effective. by proving that the average result of student motivation after the application of the think pair share cooperative learning model was 121,53, while before the application of the think pair share cooperative learning model was 107,40. The average learning outcomes after implementing the think pair share cooperative learning model are 85,33.